Pendidikan Karakter dalam Pembelajaran IPS di Sekolah Dasar - Acep Iyan; Acil Ridwan; Tin Rustini (Journal on Education, 2022)
Education is basically a conscious effort in developing the potential of students. Character education is an effort to shape the child's personality so that he becomes a good human being, a good citizen and a good country. So that it can anticipate the symptoms of the crisis that the country will face along with the times. Social studies education is a subject that examines social life whose material is based on studies of history, geography, economics, sociology, anthropology and state administration. Through social science learning, character education values ​​can be included by integrating the material in the social science learning.